Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s13197-012-0694-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different processing techniques on nutritional characteristics of oat (Avena sativa) grains and formulated weaning mixes

Abstract: One of the variety of oat, UPO 94 was processed by two simple processing techniques. One method is malting and other is roasting. Malted and roasted oat flour as well as weaning mixes prepared from these two processed flour were analyzed for their nutrient composition, alpha amylase activity and in-vitro protein digestibility. For making weaning mix, oat flour, wheat flour, green gram and skim milk powder were taken in a ratio of 30:30:25:15 respectively. Higher moisture, ash, crude fat, energy, amylase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Therefore, implementing modern agricultural practices and/or developing new varieties of pathogen-resistant oats would be necessary to prevent pathogens attacks. We can also note that different processing techniques on oats such as malting and roasting can help in keeping their high nutritive value and their resulting weaning mixes; it is also found that both oat roasted and malted weaning gruels are accepted by the panel members of sensory quality evaluation 26 . Thus, child malnutrition, caused by the introduction of traditional weaning foods, would be improved by simple processing techniques on cereals such as oats whose formulated weaning mix is being increased in nutritional value 26,27 .…”
Section: Nutritional Value Of Oat (Avena Sativa L)mentioning
confidence: 81%
“…Therefore, implementing modern agricultural practices and/or developing new varieties of pathogen-resistant oats would be necessary to prevent pathogens attacks. We can also note that different processing techniques on oats such as malting and roasting can help in keeping their high nutritive value and their resulting weaning mixes; it is also found that both oat roasted and malted weaning gruels are accepted by the panel members of sensory quality evaluation 26 . Thus, child malnutrition, caused by the introduction of traditional weaning foods, would be improved by simple processing techniques on cereals such as oats whose formulated weaning mix is being increased in nutritional value 26,27 .…”
Section: Nutritional Value Of Oat (Avena Sativa L)mentioning
confidence: 81%
“…The nutritional characteristics can be influenced by processing method (Tiwari and Awasthi 2012). Fermentation, as a common processing method, has been used for centuries to improve the nutritional value of foods.…”
Section: Introductionmentioning
confidence: 99%
“…Addis et al (2013) [1] formulated complementary food from processed sorghum, pigeon pea, soybean along with skimmed milk and sucrose in the proportion of 65:15:10:5:5. Tiwari & Awasthi (2014) [16] developed weaning mix, using oat flour, wheat flour, green gram and skim milk powder and found acceptable by panel member. 2).…”
Section: Sensory Characteristics Of Mixed Cereal Ready-to-cook (Rtc) Convenient MIXmentioning
confidence: 99%